Influence of customer relationship management, technology innovation and customer empowerment on customer loyalty in Kuwaiti banks - Aldaihani, Faraj Mazyed Faraj (2021)
Prior works on Kuwaiti banks showed that local banks face numerous challenges. An example of such challenges is customer shift to foreign banks. A key reason behind this challenge is the lack of effective digital banking services, which results in lower levels of customer satisfaction and hence customer loyalty. As a result, research in this regard emphasized that local banks should understand customer needs in order to maintain a long relationship with their customers. Previous studies underlined the importance of CRM in elevating customer loyalty, technology innovation in boosting customer relationships, and customer empowerment in enhancing customer loyalty. However, no empirical evidence was found in the literature on the influence of CRM on customer loyalty in the presence of technology innovation and customer empowerment. Therefore, the main purpose of the current research was to examine the influence of technology innovation and customer empowerment in the relationship between CRM and customer loyalty in Kuwaiti local banks. This research applied a quantitative methodology to test the relationship between variables. Convenience sampling method was used to select the right respondents for the survey using questionnaires. However, 413 valid questionnaires were collected from the 460 distributed questionnaires to customers of the Kuwaiti local banks. Adapting the Structural Equation Modelling (SEM), a structural model was constructed to test five main hypotheses including four sub hypotheses by IBM AMOS Version 22.0. The results revealed that CRM as measured by information sharing, customer involvement, knowledge management, and technology-based CRM exerted a significant influence on customer loyalty. Specifically, it was found that all dimensions of CRM had significant influences on customer loyalty. On the other hand, there was a significant causal relationship between CRM and technology innovation. Additionally, CRM has a significant direct effect on technology innovation, which in turn showed a significant direct influence on customer loyalty. Hence, CRM had direct and indirect influences on customer loyalty. Such results confirmed that technology innovation played a significant mediating role in the influence of CRM on customer loyalty. However, the results revealed that customer empowerment had no significant role in moderating the effect of CRM on customer loyalty. The study contributes to the existing literature through providing an evidence on the ground of the relationship marketing theory about the relationship between CRM and customer loyalty among customers of Kuwaiti banks. Moreover, it was found on the basis of resource-based view that if right resources are applied, banks are able to exploit more form customers. Regarding the equity theory, the results indicated that customer empowerment had a significant effect on customer loyalty but had no moderating role in the influence of CRM on customer loyalty. Based on these results, policy makers are required to effectively allocate resources and make wise decisions to increase customer loyalty through implementing CRM practices. They should integrate technology innovation in CRM approaches in order to develop customer loyalty.